PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA STRATA SATU (S1) STIE NOBEL INDONESIA DI MAKASSAR - Fitriani Latief (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The method used is descriptive quantitative method, this research using primary data and secondary data which generated from the distribution of questionnaires, interviews, direct observation and literature study. The analytical tool used in this research is a statistical analysis with multiple linear regression analysis. The hypothesis verification through t test to prove the relationship between independent variables with the dependent variable partially and to prove the relationship between dependent and independent variables simultaneously used f test analysis. The sample used in this research was 85 respondents taken from 587 student population at STIE Nobel who get active status on 2014-2015. This study proves that there is a positive and significant influence between the variables of tangibility, reliability, responsiveness, assurance and empathy (partially) to the satisfaction of the students at STIE Nobel Indonesia. The study also proves that there is a positive and significant influence between the variables of tangibility, reliability, responsiveness, assurance and empathy (simultaneously) to the satisfaction of the students at STIE Nobel Indonesia. The study also shows that the variable appearance of the product (tangibility) is the most dominant variable affecting the level of student satisfaction at Nobel STIE Indonesia.